O Sistema de franquia na organização pública: o caso da Empresa Brasileira de Correios e Telégrafos - Azevedo, Aída Helena Cerqueira de (1999)
The purpose of this work is to describe the franchising system lU its general aspect inside the actual brazilian economical conjucture, which reduction in govemment spendings and privatization and public tender processes are being implemented, and are used as the most important factors to the competition, the industry and the public services updated facing up with the globalization scenario. It was intended to make a revision of the conceptual part of the franchising system and the public organizations. The ECT - Brazilian Mail&Telegraph Company is a real study case of a public organization making use of the franchising system in large scale and successfully. In addition to this presentation, it was wanted to demonstrate other types of association between the private company and the public organization, through the public tender, privatization and outsourcing, in order to supply services and products to the costumer with better quality and less investments to the govemment.